First report of a carbapenem-resistant Serratia sarumanii clinical strain co-harboring blaKPC-2 and blaNDM-1 genes in China - Xiao Liu; Zhen Liu; Xuemei Bai; He Gao; Zhiwen Sun; Duochun Wang (Current Research in Microbial Sciences)
Carbapenem-resistant Enterobacteriaceae (CRE), particularly those co-harboring multiple carbapenemase genes, pose a significant global health threat. However, the coexistence of blaKPC-2 and blaNDM-1 in Serratia sarumanii has not been previously reported. This study aims to report and characterize the first carbapenem-resistant S. sarumanii (CRSS) clinical strain MAS3954 in China co-harboring blaKPC-2 and blaNDM-1, focusing on its genetic characteristics, plasmid stability, and transfer potential. Whole-genome analysis revealed that the blaKPC-2 and blaNDM-1 were located on two distinct plasmids. Plasmid pMAS3954-KPC (113,856 bp, IncFII/IncFIB) exhibited low similarity (<66%) to known plasmids, indicating a novel fusion event between pKPC-h2 and S. marcescens chromosome, while pMAS3954-NDM (55,235 bp, IncX3) was highly conserved (100% identity/coverage). Conjugation experiments showed that the blaNDM-1 was transferable, while blaKPC-2 was not. During 10 days of continuous passage, the genetic context of blaNDM-1 was gradually excised from the plasmids after the 8th day, whereas they maintained 100% retention for blaKPC-2. S. sarumanii MAS3954 was multidrug-resistant (MDR), including carbapenems, β-lactams, β-lactam/β-lactamase inhibitors, trimethoprim-sulfamethoxazole, tetracycline, nitrofurantoin, colistin, and fluoroquinolones, but remained susceptible to certain aminoglycosides and tigecycline. Phylogenomic analysis identified a distinct clade for S. sarumanii MAS3954, diverging notably from other strains. Comparison of resistance genes further highlighted the unique co-harboring of blaKPC-2 and blaNDM-1 in MAS3954, absent in other strains. To our knowledge, this study represents the first characterization of clinical S. sarumanii strain co-harboring blaKPC-2 and blaNDM-1. The findings highlight the need for enhanced surveillance and infection control to prevent the spread of these MDR strains in healthcare settings.